El desencuentro entre Suárez y Báñez en torno a la polémica de Auxiliis - Jaime Vilarroig Martín (Franciscanum, 2019)
In 1594 Father Suárez writes in Spanish a memorial for the public in general where he gives his view about the controversy de auxiliis. The memorial arises the wrath of the Dominicans and other orders because it’s a tendentiously vulgarization that should be reserved for theologians. For this reason the Dominican Domingo Báñez writes in the same year (1594) a refutation of Suárez's memorial, also in Spanish, addressed to the Inquisition. This article studies both documents especially relevant to philosophical hispanism for several reasons: they are thought and written in Spanish, the vehicular language besides the Latin of the high theological speculations of that time; they constitute a moment of conceptual clarification by Suarez in the configuration of his own system: the congruism; they functioned as the embryo of Bañez’s Apologia; and they are a splendid and synthetic introduction to the problem for public in general.